(untitled) (Journal of Scientific Research, 2014)
Some ternary complexes of curcumin have been synthesized by the reaction of M(II) nitrate with curcumin as primary ligand and 1,10-phenanthroline (phen) as supporting ligand in water/ethanol solution under a nitrogen atmosphere. The composition of the complexes has been characterized by elemental analysis, molar conductivity, thermogravimetric analysis, IR, UVvis spectroscopy. The results reveal that curcumin ligand coordinates with M(II) in bidentate mode after deprotonation. The supporting ligand (phen) uses its two N atoms in coordination with metal ions in bidentate mode. The general formula of the complexes is [M(Cur)(phen)]NO3 (M = Ni(II), Co(II), Cu(II) and Z(II)). The results of antibacterial activity indicated that the complexes have good antibacterial ability for the testing bacterium than that of curcumin. Furthermore, the [M(Cur)(phen)]NO3 complexes were evaluated for its in vitro anticancer activity against hepatocellular carcinoma. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.18750 J. Sci. Res. 6 (3), 509-519 (2014)